The Relationship Between Nursing Services and Psychological Well-Being in The Elderly - Diana Pefbrianti; Diana Hardiyanti (CV. Inara, 2026)
The elderly can experience psychological problems, such as feelings of uselessness and being unnecessary, changes in lifestyle, and feelings of sadness and loneliness due to the loss of a life partner and peers. One important aspect that can maintain a balanced quality of life for the elderly is psychological well-being. for this reason optimal care services are required. The purpose of this study was to see The Relationship Between Nursing Services And Psychological Well-Being In The Elderly. The design of this study used analytical descriptive correlation with cross sectional approach with a large sample of 80 respondents. The sampling technique used is total sampling with independent variables, namely nursing services, Dependent variable in this study were psychological well being. The research instruments used are nursing services questionnaire and psychological well being questionnaire. The research was carried out at the Budi Sejahtera Banjarbaru Elderly Social Protection and Rehabilitation Institution (PPRSLU). The statistical test used in this study was spearman rho test. The test results found that There was no relationship between nursing services and psychological well being. Nurses should be able to improve the provision of nursing services to the elderly in order to improve the well-being of the elderly. There is an increase in the quality of life of the elderly. The quality of life of the elderly.